SWOT analysis of the marketing of badminton premier league of Islamic Republic of Iran - Nasrollah Sajjadi, S.; Rajabi, H.; Hamidi, M.; Hajizadeh, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The present study was aimed at SWOT analysis of the marketing of badminton premier league. It was a descriptive-analytical study. The statistical population included 120 individuals who were experts, reporters, coaches and supervisors, and vice-presidents of the provincial boards among whom 92 individuals were selected as the study sample by a stratified random sampling method. Data collection was carried out using a researcher-designed SWOT questionnaire that was confirmed by 10 university and academic experts. The reliability of the questionnaire was confirmed based on a primary study on 30 individuals (Cronbach’s Alpha α=0.88). The results indicated that marketing of badminton premier league had 10 strengths, 10 weaknesses, and 10 threats, and it is recommended that opportunities should be utilized to turn threats to opportunity and weaknesses to strengths in order to have a more dynamic league.